THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND LEVERAGE COMPANY VALUES WITH INSTITUTIONAL OWNERSHIP AS MODERATION VARIABLES IN MANUFACTURING COMPANIES - Melisa Dwirahmawati; Dian Oktarina (Ecopreneur.12, 2023)
The purpose of this research is to determine the effect of corporate social responsibility and leverage on firm value with institutional ownership as moderating variable. The population in this study were manufature companies listed on the Indonesia Stock Exchange in 2016 â€“ 2020. The technique used in sample selection was purposive sampling and obtained 311 samples. Data analysis was performed using the SPSS 26 test tool by testing descriptive statistics, normality test, heterkedacity test, multiclinearity, autocorrelation, f test, R2 test, t test and Moderated Regression Analysis. The results of this study state that corporate social responsibility have no effect on firm value. Leverage have a positive effect on firm value. The ownership institutional can not moderate relationship between corporate social responsibility and leverage on firm value.Â